IDNLearn.com offers a user-friendly platform for finding and sharing knowledge. Discover trustworthy solutions to your questions quickly and accurately with help from our dedicated community of experts.
Sagot :
To find the standard form of the equation of the ellipse with the given foci and vertices, we need to follow a series of steps systematically. Let's break it down:
### Step 1: Identify Key Values
- Distance between the foci: The given foci are [tex]\( (-6, 0) \)[/tex] and [tex]\( (6, 0) \)[/tex]. The distance between these points is given by:
[tex]\[ \text{Distance between foci} = 2c = 6 - (-6) = 12 \][/tex]
Therefore, the distance [tex]\( c \)[/tex] is:
[tex]\[ c = \frac{12}{2} = 6 \][/tex]
- Distance between the vertices: The given vertices are [tex]\( (-9, 0) \)[/tex] and [tex]\( (9, 0) \)[/tex]. The total distance between these points is:
[tex]\[ \text{Distance between vertices} = 2a = 9 - (-9) = 18 \][/tex]
Therefore, the distance [tex]\( a \)[/tex] is:
[tex]\[ a = \frac{18}{2} = 9 \][/tex]
### Step 2: Use the Relationship in Ellipses
For an ellipse, the relationship between [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] is given by
[tex]\[ c^2 = a^2 - b^2 \][/tex]
Here, we already know [tex]\( a = 9 \)[/tex] and [tex]\( c = 6 \)[/tex]. We can use these values to find [tex]\( b \)[/tex].
### Step 3: Calculate [tex]\( b \)[/tex]
First, compute [tex]\( a^2 \)[/tex]:
[tex]\[ a^2 = 9^2 = 81 \][/tex]
Next, compute [tex]\( c^2 \)[/tex]:
[tex]\[ c^2 = 6^2 = 36 \][/tex]
Now, solve for [tex]\( b^2 \)[/tex]:
[tex]\[ b^2 = a^2 - c^2 = 81 - 36 = 45 \][/tex]
Finally, take the square root to find [tex]\( b \)[/tex]:
[tex]\[ b = \sqrt{45} \approx 6.708 \][/tex]
### Step 4: Write the Equation in Standard Form
The standard form of an ellipse equation with its center at [tex]\( (h, k) \)[/tex], major axis along the x-axis, and lengths [tex]\( a \)[/tex] and [tex]\( b \)[/tex] is:
[tex]\[ \frac{(x - h)^2}{a^2} + \frac{(y - k)^2}{b^2} = 1 \][/tex]
Given the center is at [tex]\( (0, 0) \)[/tex], [tex]\( h = 0 \)[/tex] and [tex]\( k = 0 \)[/tex]. Substitute [tex]\( a^2 \)[/tex] and [tex]\( b^2 \)[/tex] into the equation:
[tex]\[ \frac{(x - 0)^2}{81} + \frac{(y - 0)^2}{45} = 1 \][/tex]
Therefore, the standard form of the equation of the ellipse is:
[tex]\[ \left( \frac{x^2}{81} \right) + \left( \frac{y^2}{45} \right) = 1 \][/tex]
This is your final equation for the ellipse given the specified foci and vertices.
### Step 1: Identify Key Values
- Distance between the foci: The given foci are [tex]\( (-6, 0) \)[/tex] and [tex]\( (6, 0) \)[/tex]. The distance between these points is given by:
[tex]\[ \text{Distance between foci} = 2c = 6 - (-6) = 12 \][/tex]
Therefore, the distance [tex]\( c \)[/tex] is:
[tex]\[ c = \frac{12}{2} = 6 \][/tex]
- Distance between the vertices: The given vertices are [tex]\( (-9, 0) \)[/tex] and [tex]\( (9, 0) \)[/tex]. The total distance between these points is:
[tex]\[ \text{Distance between vertices} = 2a = 9 - (-9) = 18 \][/tex]
Therefore, the distance [tex]\( a \)[/tex] is:
[tex]\[ a = \frac{18}{2} = 9 \][/tex]
### Step 2: Use the Relationship in Ellipses
For an ellipse, the relationship between [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] is given by
[tex]\[ c^2 = a^2 - b^2 \][/tex]
Here, we already know [tex]\( a = 9 \)[/tex] and [tex]\( c = 6 \)[/tex]. We can use these values to find [tex]\( b \)[/tex].
### Step 3: Calculate [tex]\( b \)[/tex]
First, compute [tex]\( a^2 \)[/tex]:
[tex]\[ a^2 = 9^2 = 81 \][/tex]
Next, compute [tex]\( c^2 \)[/tex]:
[tex]\[ c^2 = 6^2 = 36 \][/tex]
Now, solve for [tex]\( b^2 \)[/tex]:
[tex]\[ b^2 = a^2 - c^2 = 81 - 36 = 45 \][/tex]
Finally, take the square root to find [tex]\( b \)[/tex]:
[tex]\[ b = \sqrt{45} \approx 6.708 \][/tex]
### Step 4: Write the Equation in Standard Form
The standard form of an ellipse equation with its center at [tex]\( (h, k) \)[/tex], major axis along the x-axis, and lengths [tex]\( a \)[/tex] and [tex]\( b \)[/tex] is:
[tex]\[ \frac{(x - h)^2}{a^2} + \frac{(y - k)^2}{b^2} = 1 \][/tex]
Given the center is at [tex]\( (0, 0) \)[/tex], [tex]\( h = 0 \)[/tex] and [tex]\( k = 0 \)[/tex]. Substitute [tex]\( a^2 \)[/tex] and [tex]\( b^2 \)[/tex] into the equation:
[tex]\[ \frac{(x - 0)^2}{81} + \frac{(y - 0)^2}{45} = 1 \][/tex]
Therefore, the standard form of the equation of the ellipse is:
[tex]\[ \left( \frac{x^2}{81} \right) + \left( \frac{y^2}{45} \right) = 1 \][/tex]
This is your final equation for the ellipse given the specified foci and vertices.
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Your questions deserve precise answers. Thank you for visiting IDNLearn.com, and see you again soon for more helpful information.